A mononuclear divalent ytterbium hydrido complex supported by a super-bulky scorpionate ligand. Issue 78 (10th September 2021) - Shi, Xianghui; Deng, Peng; Rajeshkumar, Thayalan; Zhao, Lanxiao; Maron, Laurent; Cheng, Jianhua
Abstract : The first mononuclear divalent ytterbium hydride complex [(Tp Ad, iPr )Yb(H)(THF)] (Tp Ad, iPr = hydrotris(3-adamantyl-5-isopropyl-pyrazolyl)borate) (2 ) bearing a terminal hydrido ligand was obtained by hydrogenolysis of the benzyl precursor in hexane. Abstract : The first mononuclear divalent ytterbium hydride complex [(Tp Ad, iPr )Yb(H)(THF)] (Tp Ad, iPr = hydrotris(3-adamantyl-5-isopropyl-pyrazolyl)borate) (2 ) bearing a terminal hydrido ligand was obtained by hydrogenolysis of the benzyl precursor in hexane. Complex 2 exhibited two different reaction patterns towards allenes: Yb–H addition with cyclohexylallene and deprotonation of 1, 1-dimethylallene.